Brucea javanica oil emulsion plus supportive care for refractory advanced colorectal cancer: a pilot RCT protocol - Liyuan Fang; Yan Wang; Yuhang Fang; Runxi Wang; Yi Xie; Shuhan Yang; Suying Liu; Ying Zhang (Frontiers in Pharmacology)
BackgroundColorectal cancer (CRC) is a significant contributor to global mortality. However, the existing therapeutic approaches often fall short of achieving favorable outcomes especially in metastatic CRC. Brucea javanica Oil Emulsion Injection (BJOEI) as adjuvant therapy also showed superiority for cancer treatment in clinical practice. This trial aims to gather preliminary data to inform a phase III clinical trial evaluating the efficacy and safety of BJOEI in combination with best supportive care (BSC) for patients with advanced colorectal cancer who are refractory to all existing therapies.MethodsThe study is designed as a multicenter, randomized, and controlled clinical trial. 60 eligible participants will be randomly assigned to the experimental or control group in a ratio of 1:1. The experimental group will receive BJOEI and BSC, while the control group will undergo BSC. The treatment will cease upon disease progression or when toxicity becomes intolerable. Follow-up assessments will be scheduled every 2 months, continuing until the patient dies, is lost to follow-up, or reaches 12 months post-randomization. The main outcome measured will be progression-free survival (PFS). Additional outcomes to be evaluated are clinical symptoms, quality of life, and overall survival (OS). Detailed records of adverse events (AEs) will be maintained.Expected outcomesTo the best of our knowledge, this is the first study to investigate the use of Traditional Chinese Medicine as a monotherapy in patients with advanced colorectal cancer who have failed multiple lines of standard treatment.Trial registrationClinicaltrials.gov, NCT05897749. Registered on 09 May 2023.